Synthesis and Characterization of Some New Derivatives of Thiourea and Study of Their Biological Activity - Miad Hassan Jebur (Journal of Global Pharma Technology, 2016)
Some new derivatives of Suberyl Chloride  synthesized by reacting with ammonium  thiocyanate then the product is reacting with some amino acids to prepare thioureio-amino acid,  as well as react with two amino hetrocyclic compounds are 2-aminobenzo[d]thiozole-6-carboxylic acid and thiophen-2-amine to prepare thiourea derivatives. This reaction was checked by thin‐layer chromatography (TLC) method. All new compounds were characterized by melting points, elemental analysis, FT‐IR and 1H&13C-NMR. The antibacterial action of these derivatives was also determined as well as study three of these derivatives as anti-breast cancer. Keywords: Suberyl Chloride, thioureio-amino acid, antibacterial, thiourea derivatives, anti-breast cancer.